The use of infrared thermography for the dynamic measurement of skin temperature of moving athletes during competition; methodological issues. (27th August 2021) - Aylwin, Polly E; Racinais, Sebastien; Bermon, Stéphane; Lloyd, Alex; Hodder, Simon; Havenith, George
Abstract: Objective . To investigate the use of infrared thermography (IRT) for skin temperature measurement of moving athletes during competition and its sensitivity to factors that are traditionally standardised. Approach . Thermograms were collected for 18 female athletes during the 20 km racewalk at the 2019 World Athletics Championships, with a medium-wave, cooled indium antimonide medium wave infrared band (MWIR) and a long-wave, uncooled microbolometer longwave infrared band (LWIR) infrared camera. Main results . The MWIR provided greater clarity images of motion due to a shorter exposure and response time and produced a higher percentage of acceptable images. Analysing acceptable images only, the LWIR and WMIR produced good levels of agreement, with a bias of −0.1 ± 0.6 °C in mean skin temperature for the LWIR. As the surface area of an ROI was reduced, the measured temperature became less representative of the whole ROI. Compared to measuring the whole area ROI, a single central pixel produced a bias of 0.3 ± 0.3 °C (MWIR) and 0.1 ± 0.4 °C (LWIR) whilst using the maximum and minimum temperature pixels resulted in deviations of 1.3 ± 0.4 °C and −1.1 ± 0.3 °C (MWIR) and 1.2 ± 0.3 °C and −1.3 ± 0.4 °C (LWIR). The sensitivity to air and reflected temperatures was lower for the LWIR camera, due to the higher emissivity of skin in its wavelength. Significance . IRT provides an appropriate tool for the measurement of skin temperature during real-world competition and critically during athlete motion. The cheaper LWIR camera provides a feasible alternative to the MWIR in low rate of motion scenarios, with comparable precision and sensitivity to analysis. However, the LWIR is limited when higher speeds prevent the accurate measurement and ability to capture motion.